2011
DOI: 10.1177/0146167210392384
|View full text |Cite
|
Sign up to set email alerts
|

From “In the Air” to “Under the Skin”: Cortisol Responses to Social Identity Threat

Abstract: The authors examined women’s neuroendocrine stress responses associated with sexism. They predicted that, when being evaluated by a man, women who chronically perceive more sexism would experience more stress unless the situation contained overt cues that sexism would not occur. The authors measured stress as the end product of the primary stress system linked to social evaluative threat—the hypothalamic–pituitary–adrenal cortical axis. In Study 1, female participants were rejected by a male confederate in fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 69 publications
5
83
0
1
Order By: Relevance
“…Importantly, however, cortisol secretion does occur in other socially stigmatized domains. For example, Townsend, Major, Gangi, and Mendes (2011) found that, among women high in chronic perceptions of sexism, interacting with an ostensibly sexist man represented a stressor that resulted in increased cortisol secretion. In the weight stigma domain, only two studies have examined cortisol in relation to experiencing weight stigma.…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…Importantly, however, cortisol secretion does occur in other socially stigmatized domains. For example, Townsend, Major, Gangi, and Mendes (2011) found that, among women high in chronic perceptions of sexism, interacting with an ostensibly sexist man represented a stressor that resulted in increased cortisol secretion. In the weight stigma domain, only two studies have examined cortisol in relation to experiencing weight stigma.…”
Section: Physiological Mechanismsmentioning
confidence: 99%
“…Women's experiences of discrimination are associated with depression, reduced self-esteem, subjective well-being (Branscombe, Schmitt & Harvey, 1999;Foster, 2009a;Klonoff, Landrine & Campbell, 2000;Moradi & Subich, 2002) and physical disturbances like negative health behaviours, physical pain, and stress-reactive hormones (Matheson & Anisman, 2009;Townsend, Major, Gangi & Mendes, 2011;Zucker & Landry, 2007). It is therefore important to identify ways to reduce the negative effects of discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…Within this literature, perceived sexism has been associated with many negative health-related outcomes, such as binge drinking, cigarette smoking, and premenstrual symptoms (Landrine et al 1995;Zucker and Landry 2007). Experimental studies have corroborated these cross-sectional findings, showing that women who have experienced sexism exhibit heightened cardiovascular reactivity and cortisol levels-risk factors for hypertension and cardiovascular disease-compared to those who have not (Eliezer, Major, and Mendes 2010;Townsend et al 2011).…”
Section: Sexism and Women's Healthmentioning
confidence: 93%
“…Typically, women perceive hostile sexism negatively, and as a result of being the target of such unfair treatment, experience anger, distress, and physiological arousal and are more likely to engage in collective action on behalf of women (e.g., Becker and Wright 2011;Brinkman, Garcia, and Rickard 2011;Townsend et al 2011). Contrary to these responses, exposure to benevolent sexism instead often leads women to react relatively more positively and engage in stereotypically feminine behaviors unwittingly.…”
Section: Differentiating Between Hostile and Benevolent Sexismmentioning
confidence: 99%